Investigation of Shallow Paleochannel in Banda Aceh based on Electrical Resistivity Tomography - Muzakir Zainal; Muhammad Yanis; Umar Muksin; Nazli Ismail (Journal of Aceh Physics Society, 2017)
Pembentukan daratan pesisir sangat dipengaruhi oleh proses sedimentasi dari material hasil rombakan. Proses sedimentasi pada masa lampau dapat dikaji dengan mempelajari sungai purba sebagai media transportasi material. Survey geofisika metode electrical resistivty tomography dilakukan untuk investigasi sungai purba di Ulee Kareng Banda Aceh. Untuk memetakan sedimen dan geometri sungai purba, pengukuran electrical resistivity dilakukan di sepanjang dua lintasan dengan panjang 240 meter dan spasi elektroda 2 meter. Proses inversi model resistivitas 2D telah dilakukan pada masing – masing lintasan data yang terukur. Hasil electrical resistivity tomography mampu membedakan batas – batas antara setiap lapisan sedimen yang terendapkan di lokasi paleochannel. Sedimen paleochannel secara jelas diidentifikasi dari distribusi nilai resistivitas yang lebih tinggi (15.2–31.6 Ω.m). Berdasarkan interpretasi dari metode electrical resistivity tomography area persawahan merupakan lokasi sungai purba pada masa lampau. The formation of coastal area is influenced by sedimentation process. The sedimentation process along the coastal line in the past one can be explained by studying existence of paleochannels located around the area. Deposition of the sediment along the coast is carried by river activities in the past. We have investigated paleochannel structure in Ulee Kareng, Banda Aceh using electrical resistivity tomography survey. The measurements were performed along two profiles with 240 meters and 2 meters spacing between electrodes crossing the paddy. The method measured apparent resistivity data along the profiles. The 2D resistivity models were inverted from the apparent resistivity data using Res2Div program. The inverted models clearly show indication of paleochannel structure based on distribution of resistivity values within the subsurface. The paleochannel area was characterize by high resistivity i.e. 15.2–31.6 Ω.m.